Developing an Islamic Integrative Science and Religious Curriculum: Case of Sekolah Dasar Islam Terpadu Al-Uswah - Ufie Islachah; Nadlir; Aning Wida Yanti (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Metro, 2026)
The integration of science and religion synthesizes empirical knowledge and faith-based values ​​in education. While studies on Islamic-based integrative curriculum have grown, several prior investigations have comprehensively examined the entire curriculum development cycle encompassing planning, implementation, and evaluation, as well as facilitating and hindering factors for both Science Learning and Islamic Religious Education within a single integrated Islamic elementary school through an in-depth case study. This research addresses that gap by examining the implementation of an Islamic-based integrative curriculum at SD Islam Terpadu Al-Uswah Surabaya, Indonesia. Employing a qualitative case study design, data were collected from eight purposively selected participants using in-depth interviews, classroom observations, and document analysis. Data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, while data credibility was ensured through source and technique triangulation, member checking, and researcher reflexivity. The research findings indicate that: (1) the curriculum is systematically designed through collaborative planning between Science and Islamic Religious Education teachers, formally integrating tawhid (monotheism) and moral values ​​into learning competencies within the framework of the Kurikulum Merdeka (Independent Curriculum); (2) instruction is contextual, reflective, and interactive, addressing scientific phenomena alongside Quranic verses; (3) facilitating factors include institutional commitment, teacher collaboration, and a religious school culture, whereas primary obstacles include time constraints, a scarcity of integrative resources, and uneven cross-disciplinary teacher readiness; and (4) holistic evaluation encompasses cognitive, affective, psychomotor, and spiritual dimensions. These findings offer a replicable integrative curriculum model designed to enhance academic competence while fostering religious character development in Islamic primary education.